Zhongyong Thinking Style and Resilience Capacity in Chinese Undergraduates: The Chain Mediating Role of Cognitive Reappraisal and Positive Affect - Zhou, Shisi; Li, Xueping (Frontiers in Psychology, 2022)
Abstract: Previous studies have suggested that Zhongyong thinking style(influenced by Chinese culture) is associated with psychological features. However, little is known about the direct association between Zhongyong thinking and resilience and the underlying mechanisms of this relationship in Chinese culture. The present study aimed to investigate the association between Zhongyong thinking and undergraduates’ resilience and to assess whether cognitive reappraisal and positive affect mediated this association. A sample of undergraduates (n=1356, 70.4%female，mean age=19 years) was recruited in this study and completed the Zhongyong Thinking Style Scale (ZYTS), the Emotion Regulation Questionnaire (ERQ), the Positive Affect and Negative Affect Scale (PANAS), and the Resilience-11. Results indicated that Zhongyong thinking style was positively and significantly associated with resilience. Undergraduates’ resilience was affected by Zhongyong thinking partly through 3 different pathways: the mediating role of cognitive reappraisal, the mediating role of positive affect, and the mediating chain role of both cognitive reappraisal and positive affect. These findings might provide a deeper understanding of the protective factors for resilience among Chinese undergraduates.